Helichrysum nudifolium (L.) Less.: Review of its Medicinal Uses, Phytochemistry and Biological Activities - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2019)
Helichrysum nudifolium is a valuable and well-known medicinal plant species in southern Africa. The current study critically reviewed the medicinal uses, phytochemistry and biological activities of H. nudifolium. Information on medicinal uses, phytochemistry and biological activities of H. nudifolium was collected from multiple internet sources which included Scopus, Google Scholar, Elsevier, Science Direct, Web of Science, Pubmed, SciFinder and BMC. Additional information was gathered from pre-electronic sources such as journal articles, scientific reports, theses, books and book chapters obtained from the University library. This study showed that H. nudifolium is mainly used as ethnoveterinary medicine, as colic and herbal medicine for fever, headache, swellings, infertility, pregnancy and postpartum problems. Pharmacological research revealed that H. nudifolium extracts have antibacterial, antimycobacterial, antifungal, anti-HIV, GABAA-benzodiazepine receptor-binding, anticancer, anti-inflammatory, antiplasmodial, antiprotozoal and cytotoxicity activities. There is need for experimental animal studies, randomized clinical trials and target-organ toxicity studies involving H. nudifolium crude extracts and compounds isolated from the species. Future should also focus on evaluation of pharmacological properties of compounds isolated from H. nudifolium.